Advanced Microsystems for Automotive Applications 2016 Smart Systems for the Automobile of the Future - Schulze, Tim; Müller, Beate; Meyer, Gereon (Lecture Notes in Mobility, 2016)
This book contains the papers presented at the 20th anniversary edition of the AMAA conference held in Brussels, Belgium in 2016. The theme of the conference was "Smart Systems for the Automobile of the Future". The automobile is currently being reshaped at unprecedented pace. Automation and electrification are the two dominant megatrends which dramatically change the choice and design of components, systems, vehicular architectures and ultimately the way we use cars in the coming decades. Novel E/E architectures, vehicular connectivity and cloud services will be key to extending the perception and decision-making horizons of automated vehicles, to enable cooperative functions and a seamless digital user experience. The AMAA's ongoing mission to detect novel trends in automotive ICT, electronics and smart systems and to discuss the technological implications is once again reflected in this volume. The book will be a valuable read for research experts and professionals in the automotive and smart systems industry but the book may also be beneficial for graduate students.